Reactivity of Cobalt‐Fullerene Complexes towards Deuterium. Issue 10 (21st April 2020) - Vanbuel, Jan; Germán, Estefanía; Libeert, Guillaume; Veys, Koen; Moens, Janni; Alonso, Julio A.; López, María J.; Janssens, Ewald
Abstract: The adsorption of molecular deuterium (D2 ) onto charged cobalt‐fullerene‐complexes Co n C60 + ( n =1–8) is measured experimentally in a few‐collision reaction cell. The reactivity is strongly size‐dependent, hinting at clustering of the transition metal atoms on the fullerenes. Formation and desorption rate constants are obtained from the pressure‐dependent deuterogenation curves. DFT calculations indeed find that this transition metal clustering is energetically more favorable than decorating the fullerene. For n =1, D2 is predicted to bind molecularly and for n =2 dissociative and molecular configurations are quasi‐isoenergetic. For n =3–8, dissociation of D2 is thermodynamically preferred. However, reaching the ground state configuration with dissociated deuterium on the timescale of the experiment may be hindered by dissociation barriers. Abstract : The reaction kinetics of Co n C60 + ( n =1 to 8) towards deuterium is investigated in a few‐collision reaction cell. The size‐dependent reactivity hints towards Co aggregation on the fullerene surface, which is confirmed by DFT calculations. The thermodynamically favorable deuterium adsorption mechanism is molecular for n = 1, 2 and dissociative for n = 3 to 8. However, dissociation barriers may hinder reaching the ground‐state configuration within the time scale of the experiment.